1992
DOI: 10.1038/bjc.1992.226
|View full text |Cite
|
Sign up to set email alerts
|

Host cell reactivation of gamma-irradiated adenovirus 5 in human cell lines of varying radiosensitivity

Abstract: Summary DNA repair processes play an important role in the determination of radiation response in both normal and tumour cells. We have investigated one aspect of DNA repair in a number of human cell lines of varying radiosensitivity using the adenovirus 5 host cell reactivation assay (HCR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, the phenomenon of induced radioresistance has been earlier described in human lymphocytes 27 and in some other human cells. 23,28,29 In these studies, the exposure to an initial radiation dose before subsequent doses has been shown to result in a higher resistance. This has been assumed to be an evidence of cellular radioprotective mechanisms that are triggered in response to exposure to small doses of ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the phenomenon of induced radioresistance has been earlier described in human lymphocytes 27 and in some other human cells. 23,28,29 In these studies, the exposure to an initial radiation dose before subsequent doses has been shown to result in a higher resistance. This has been assumed to be an evidence of cellular radioprotective mechanisms that are triggered in response to exposure to small doses of ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it is well established that NB tumors are highly radiosensitive, making radiotherapy a major treatment modality (18,27). Likewise, undifferentiated human NB cell lines are unusually radiosensitive (8,23,33,37). In fact, high UV radiation sensitivity of NB cells was associated with very low DNA repair activity.…”
Section: Discussionmentioning
confidence: 99%
“…[46,47]). Other reports have found no evidence that A‐T cells are functionally defective in DNA repair [48,49]. On the other hand, A‐T homozygotes may have subtle defects in their ability to process DNA breaks, as the accuracy of strand rejoining appears to be impaired in A‐T cells [50,51].…”
Section: Ataxia‐telangiectasiamentioning
confidence: 97%